Comparing the effects of EMLA ointment with a diversionary activity (music) on Vein Puncture pain at school-age children - Shahabi, M; Kalani- Tehrani, D; Eghbal, M; Alavi- Majd, H; Abed Saidi, J (Advances in Nursing & Midwifery, 2009)
Abstract Introduction: Many children experience preventive, diagnostic and therapeutic procedures each day, most of which are painful. Vein Puncture is one of the most common invasive procedures performed by nurses. Experiencing pain during these procedures can have extensive adverse effects. Purpose: This cross-over clinical trial was conducted to identify and compare the effects of EMLA (Eutectic mixture of local anesthetics) ointment with music on Vein Puncture pain in school-age children at Shaheed Dastgheib Hospital in Shiraz, 2006. Materials and Methods: 46 thalassemic children referring to Shaheed Dastgheib Hospital in Shiraz was selected by convenient sampling method. Each of the subjects was randomly assigned for routine, EMLA ointment, and music methods at 14-day intervals for Vein Puncture. Data collection tools included a demographic questionnaire, CHEOPS behavior scale, Wong’s self-report scale and a checklist for possible side effects of EMLA. Content and inter-rater methods were used for validity and reliability of the tools respectively (r=0.91). Different statistical tests were used for data analysis. Results: The pain of Vein Puncture with music and EMLA ointment was significantly lower than that with the routine method (P<0.001). No significant difference was found between the amounts of pain with music and EMLA. In addition, no short-term side effect was detected with the ointment. Conclusion: Using EMLA ointment or music during Vein Puncture at school-age children can significantly reduced pain and they can be applied alternatively. Keywords: Vein Puncture, Ointment, EMLA.